Preprocedural Mean Platelet Volume Level Is a Predictor of In-Stent Restenosis of the Superficial Femoral Artery Stents in Follow-Up - Kurtulus Karauzum; Ulas Bildirici; Emir Dervis; Irem Karauzum; Canan Baydemir (Cardiology Research and Practice)
Background. The mean platelet volume (MPV), the most commonly used measure of the platelet size, is a cheap and easy-to-use marker of the platelet activation. We aimed to evaluate the relationship between preprocedural MPV and other hematologic blood count parameters and in-stent restenosis in patients with superficial femoral artery (SFA) stenting. Methods and Results. The consecutive 118 patients who successfully underwent endovascular stenting of the SFA were enrolled retrospectively in the study. The mean follow-up was 23 ± 12 months. The in-stent restenosis was observed in 42 patients (35.6%). There were no statistically significant differences between the restenosis group and no-restenosis group in terms of age, gender, and smoking (p=0.116, p=0.924, and p=0.428, resp.). In the restenosis group, the MPV level was markedly higher than that in the no-restenosis group, and it was statistically significant (p<0.001). According to the ROC curve analysis, the optimal cutoff value of the MPV to determine the restenosis was >8.7 fL, and the level of the MPV >8.7 fL was a strong predictor of the restenosis (p<0.001) in logistic regression analysis. Conclusions. The measurement of the preprocedural MPV levels may help to identify high-risk patients for development of the in-stent restenosis. These patients may benefit from an aggresive antiplatelet therapy and close follow-up.